Transformation of mothers’ values through an online multidisciplinary group consultation on pregnancy and childcare: A trajectory equifinality approach - Haruka Tani; Shoko Sugao; Yasuji Kitabatake; Masayo Matsuzaki; Goji Nakamoto; Masayuki Endo (Social Sciences and Humanities Open)
Competent parenting is vital for child development; however, mothers frequently encounter stress and loneliness, underscoring the importance of social support. The COVID-19 pandemic has amplified the focus on online support, offering accessibility and potential empowerment. However, it also poses challenges, including concerns about the reliability of online information. To address these challenges, XXXX University initiated online multidisciplinary group consultations. The present study sought to explore the impact of these consultations on maternal childcare values. Employing semi-structured interviews with five group consultation participants, data were analyzed using the Trajectory Equifinality Approach. The findings revealed that online group consultations facilitated a process of value transformation, restoring maternal security and confidence through elements such as evidence-based information from organizers, a warm atmosphere, and peer empathy. Online multidisciplinary group consultations may serve as a valuable support resource for mothers, especially amidst increasing social isolation. Moreover, future efforts should leverage these insights to build comprehensive, needs-based childcare support systems integrating both online and in-person modalities.